The protective effect of oleic acid on Lactiplantibacillus plantarum during freeze-drying - Yongjun Xia; Yizhen Wang; Jing Pu; Yan Wu; Zhiqiang Xiong; Xin Song; Hui Zhang; Lianzhong Ai; Guangqiang Wang (Food Science and Human Wellness)
Membrane characteristics are determined by the fatty acids composition, which affects survival rates after freeze-drying. However, it is unknown which composition provides the greatest effect. In this study, we found that the addition of Tween 80 and Tween 20 significantly increased survival rates of Lactiplantibacillus plantarum, which reached a maximum of 93.1 %. Conversely, Tween 60 caused a significant decrease. We further found that the difference between the effects of adding Tween 80 and Tween 60 was the change in oleic acid contents. To verify the role of oleic acid, we used CRISPR-Cas9 to knock-out the key synthesis gene cla-er. The survival rates of L. plantarum AR113Δcla-er declined to 5.48 %. The addition of oleic acid restored the rates to those of wild type strains. Moreover, the membrane integrity and fluidity of knockout strains markedly decreased. This is the first confirmation that Tween 80 or Tween 20 increases the survival rate by increasing the content of oleic acid in the cell membrane. These findings also indicated that oleic acid in cell membranes has a substantial protective effect on L. plantarum during freeze-drying.